The Value of Microblogging in Education - Terry Freedman (Formare, 2013)
In this article, Terry Freedman looks at how microblogging services such as Twitter, Edmodo and Cirip are being used in education, both in the classroom and for professional development. Although microblogging does not, at first glance, look particularly useful for teaching and learning, the opposite turns out to be the case.